Coexistence of tubo-ovarian abscess and carcinoid tumor of the appendix in a sexually inactive girl: a case report - Tuğba Acer-Demir; Müge Sağnak-Akıllı; Lütfi Hakan Güney; Esra Elif Arslan; Ender Fakıoğlu (SpringerOpen, 2022)
Abstract Background Tubo-ovarian abscess (TOA) is mostly a sequela of pelvic inflammatory disease (PID) which is seen in sexually active women. Although very rare, TOA could be seen in virgin adolescent girls. Fifteen cases of TOA were reported in virgin girls in English literature. Only one of these cases was suspected to be due to appendicitis. Herein, we present the first case of coexistence of tubo-ovarian abscess and carcinoid tumor of the appendix in a sexually inactive girl. Case presentation A 13-year-old girl presented with abdominal pain and fever. Ultrasonography reported that there was a 63×48 mm sized, heterogeneous, thick-walled, dense-content complicated cyst in the right ovary which was thought to be a hemorrhagic cyst and a tubular structure, measuring 12 mm in its thickest part which was thought to be the appendix. During the operation, a TOA was observed in the right adnexal region. The thick, edematous appendix which was lying separately was excised. The TOA was evacuated; a drain was placed. The appendix pathology was reported as "carcinoid tumor." Conclusion We present the first case of TAO with carcinoid tumor of appendix and the second case of TAO that was suspected to be due to appendicitis. When the sexually inactive TOA cases including our case were reviewed, we found that the median age was 15 years (12-47 years) and 11 of 16 cases (69%) were under 18 years of age. The presenting symptoms were abdominal or pelvic pain in all cases, fever in 11 cases (69%), vomiting in 6 cases (38%), dysuria in 5 cases (31%), and diarrhea in 3 cases (19%). Both perforated appendicitis and TOA patients have the same clinic presentation such as fever, abdominal tenderness, increased leukocyte count, increased inflammatory markers. The differential diagnosis can be achieved by radiological examinations such as ultrasonography, computerized tomography or magnetic resonance imaging.